Coordination chemistry of 2,2’-bipyridyl- and 2,2’:6’,2”-terpyridyl-substituted BEDT-TTFs: formation of a supramolecular capsule motif by the iron(II) tris complex of 2,2’-bipyridine-4-thiomethyl-BEDT-TTF - Wang, Qiang; Martin, Lee; Blake, Alexander J.; Day, Peter; Akutsu, Hiroki; Wallis, John D. (American Chemical Society, 2016)
Molecules of tris(2,2’-bipyridine-4-thiomethyl-BEDT-TTF)iron(II) (BEDT-TTF = bis(ethylenedithio)tetrathiafulvalene) assemble in pairs to form a novel supramolecular capsular structure in the solid state. Three BEDT-TTF residues from one complex lie in the three grooves between coordinated bipyridines of the other complex, and vice versa, to form a capsule with three-fold rotational symmetry and an internal volume of ca. 160 Å3. Further aspects of the coordination chemistry of this ligand, its 6-substituted isomer and the 2,2’:6’2’’- terpyridyl-4’-thiomethyl-BEDT-TTF analogue are described.